COMMENTARY ON THE OFFICIAL HISTORY OF THE YUAN DYNASTY (Web of Teachers: Inderscience Research, 2026)
This article examines the History of Yuan (Yuan Shi), the official history of the Yuan dynasty, from a critical historiographical perspective. It analyzes the main shortcomings of the text, including its rapid compilation, internal contradictions, and the limited use of Mongolian-language sources. Particular attention is given to the process of “sinicization,” through which the history of the Mongol Empire was incorporated into the framework of Chinese dynastic historiography. The study also reviews the contributions of Chinese and foreign scholars who have attempted to correct, supplement, and reinterpret the Yuan Shi. Works by historians such as Qian Daxin, Wei Yuan, Tu Ji, and Ke Shaomin are discussed as important efforts in addressing its deficiencies. In addition, the role of auxiliary texts and foreign-language sources in reconstructing a more accurate picture of Mongol history is highlighted. The article concludes that, despite its flaws, the Yuan Shi remains an essential historical source, but it must be used with caution and in conjunction with other materials for a more balanced and reliable interpretation of the Yuan dynasty and the Mongol Empire.